2016
DOI: 10.21010/ajtcam.v14i1.6
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Anti-Inflammatory Effects of Taraxasterol Against Animal Models

Abstract: contributed equally to this study. AbstractBackground: Traditional Chinese medicine Taraxacum officinale has been widely used to treat various inflammatory diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
(7 reference statements)
0
5
0
1
Order By: Relevance
“…Herba Taraxaci Mongolici, Flos Carthami, and Semen Coicis are related to inflammatory index, such as ESR and CRP. The new research demonstrated that taraxasterol has the in vitro anti-inflammatory effect, which is one of the chief active components isolated from Herba Taraxaci Mongolici [ 21 ]. Flos Carthami [ 22 ] and Semen Coicis [ 23 ] are perhaps connected to its antioxidation and anti-inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…Herba Taraxaci Mongolici, Flos Carthami, and Semen Coicis are related to inflammatory index, such as ESR and CRP. The new research demonstrated that taraxasterol has the in vitro anti-inflammatory effect, which is one of the chief active components isolated from Herba Taraxaci Mongolici [ 21 ]. Flos Carthami [ 22 ] and Semen Coicis [ 23 ] are perhaps connected to its antioxidation and anti-inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, ethanol increased TNF- α and IL-6 secretion, and taxarasterol significantly reduced ethanol-induced TNF- α and IL-6 secretion, indicating that taraxasterol could protect ethanol-induced liver injury by involving antagonism of proinflammatory cytokines. Many of our previous studies have also shown that taraxasterol has the in vitro and in vivo anti-inflammatory activity by suppressing the production of various inflammatory cytokines and mediators [ 15 , 17 19 , 34 ]. The present data are consistent with our previous studies.…”
Section: Discussionmentioning
confidence: 99%
“… 73 After sacrifice, the weight of granuloma, the expression of inflammatory mediators (proinflammatory cytokines, NO and so on) and the level of ROS related indexes are assessed to evaluate anti‐inflammatory activity. The anti‐inflammatory effect of Taraxacum officinale , 83 Ipomoea stolonifera 73 and Qingdaisan (Formulated Indigo powder) 84 has been confirmed in a cotton pellet‐induced granuloma model. Thus, granuloma is a widely used model for the assessment of chronic anti‐inflammatory activity of TCM.…”
Section: The Classical Experimental Model Of the Anti‐inflammatory Ef...mentioning
confidence: 89%